Sistem Pengenalan Telapak Tangan pada Interaksi Manusia Robot sebagai Perintah untuk Mobile Robot - Panji Setyo Suharso (Syntax Literate, 2023)
Palm recognition system on human-robot interaction as commands for mobile robots is aresearch that aims to develop a system that allows robots to receive commands and instructions non-verbally from humans through palm recognition. Using image recognition and data processing technology, the system aims to create an intuitive interaction between humans and robots, allowing robots to recognize hand gestures and understand commands given. The research includes several stages of development. First, image processing and analysis is carried out to identify and understand the shape and movement of the human palm. Then, the data is linked with the appropriate commands to be communicated to the mobile robot. The training process is carried out to improve the accuracy of the palm recognition system and reduce the likelihood of errors in the interpretation of commands. The results of this study are expected to have a positive impact on the use of mobile robots, especially in complicated or dangerous environments where verbal communication may be limited or impossible. More natural and easy human-robot interaction is expected to improve efficiency and safety in the operation of mobile robots.